Effect of heat stress on blood biochemistry and energy metabolite of the Dazu black goats - Wang, Le; Zhang, Pengjun; Du, Yuxuan; Wang, Changtong; Zhang, Li; Yin, Li; Zuo, Fuyuan; Huang, Wenming (Frontiers in Veterinary Science, 2024)
The objective of this study was to determine the effects of heat stress (HS) on physiological, blood biochemical, and energy metabolism in Dazu black goats. Six wether adult Dazu black goats were subjected to 3 experimental periods: high HS (group H, temperature-humidity index [THI] > 88) for 15 d, moderate HS (group M, THI was 79-88) for 15 d, and no HS (group L, THI < 72) for 15 d. Rectal temperature (RT) and respiratory rate (RR) were determined on d 7 and 15 of each period, and blood samples were collected on d 15 of each period. All goats received glucose (GLU) tolerance test (GTT) and insulin (INS) tolerance test on d 7 and d 10 of each period. The results showed that HS decreased dry matter intake (DMI) and INS concentration (p < 0.05), and increased RT, RR, non-esterified fatty acid (NEFA), cortisol (COR), and total protein (TP) concentrations (p < 0.05). Compared to group L, the urea nitrogen (BUN) concentration increased and GLU concentration decreased in group H (p < 0.05). During the GTT, the area under the curve (AUC) of GLU concentrations increased by 12.26% (p > 0.05) and 40.78% (p < 0.05), and AUC of INS concentrations decreased by 26.04% and 14.41% (p < 0.05) in groups H and M compared to group L, respectively.The INS concentrations were not significant among the three groups (p > 0.05) during the ITT. A total of 60 differentially expressed metabolites were identified in response to groups H and M. In HS, changes in metabolites related to carbohydrate metabolism and glycolysis were identified (p < 0.05). The metabolites related to fatty acid βoxidation accumulated, glycogenic and ketogenic amino acids were significantly increased, while glycerophospholipid metabolites were decreased in HS (p < 0.05). HS significantly increased 1-methylhistidine, creatinine, betaine, taurine, taurolithocholic acid, inosine, and hypoxanthine, while decreasing vitamin E in blood metabolites (p < 0.05). In summary, HS changed the metabolism of fat, protein, and energy, impaired GLU tolerance, and mainly increased amino acid metabolism to provide energy in Dazu black goats.